Aerosol-Mist Coalescing Filters - a Review - Mead-Hunter, Ryan; King, Andrew; Mullins, Ben (Pergamon, 2014)
Fibrous filters and mist eliminators are widely used in a range of manufacturing and process industries worldwide to remove liquid mists from gas streams, thereby coalescing them to recover the bulk liquidand prevent emissions. The range of applications include compressed gas cleaning, engine crankcase ventilation, (liquefied) natural gas, propane (LPG) and hydrocarbon production and processing, cooling towers, machining and cutting processes and a range of other process engineering applications. Although research on mist filtration has been increasing since the late 1950s, and some of the fundamental physico-chemical processes were described as early as 1870, the scientific questions in the field are far from resolved. This is largely due to the complex kinetics of gas and fluid phases, and the wide range of possible filter geometric properties and surface energy. However, over the last 15 years, significant progress has been made in describing and modelling mist filter systems. Most models developed to date, are however empirically derived, and therefore only applicable to a narrow range of filter media and operating conditions. This paper reviews the state of current research, comparing currently available models for capture, saturation and pressure drop and discussing their applicability. Key gaps in the literature and necessary directions for future research are also given. The work also reviews published experimental data to-date, showing the range of media studied and summarising relationships which can be identified by collating results from all studies which provide sufficient data.